2013
DOI: 10.1002/hrm.21527
|View full text |Cite
|
Sign up to set email alerts
|

Internal Commitment or External Collaboration? The Impact of Human Resource Management Systems on Firm Innovation and Performance

Abstract: Complementing previous research that showed a positive effect of general human resource management (HRM) systems on general fi rm performance, this article undertakes an integrative approach to compare the main effects and examine the interaction effects of two particular HRM systems on infl uencing fi rm innovation and performance. Using data from 179 organizations in China, we found that both the commitment-oriented system, which emphasized internal cohesiveness, and the collaboration-oriented system, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(149 citation statements)
references
References 150 publications
(203 reference statements)
4
142
1
2
Order By: Relevance
“…The principal investigator (PI) and co-PI utilized the information gathered from this fieldwork to improve the protocols. Both confirmatory factor analysis and Cronbach's alpha indicate that measurement validity and reliability of the indices were satisfactory (see Appendix; Wei & Lau, 2010;Zhou, Hong, & Liu, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal investigator (PI) and co-PI utilized the information gathered from this fieldwork to improve the protocols. Both confirmatory factor analysis and Cronbach's alpha indicate that measurement validity and reliability of the indices were satisfactory (see Appendix; Wei & Lau, 2010;Zhou, Hong, & Liu, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The models were tested using hierarchical regression analyses (Boslie, 2010;Hartley et al, 2007;Iverson & Zatick, 2011;Kwon, Bae, & Lawler, 2010;Messersmith & Guthrie, 2010;Messersmith &Wales, 2011;Way, 2002;Wei & Lau, 2010;Zhou, Hong, & Liu, 2013). The tests were based on changes in the level of explained variance before and after the HPWPs were added to the model.…”
Section: Methodsmentioning
confidence: 99%
“…Other innovation boundaries are virtualmediated by ICTs (Ashurst et al, 2012). Managing contextual challenges requires adaptability (Thongpapanl et al, 2012;Weigelt and Sarkar, 2012), adaptive management (Moellenkamp et al, 2010), environmental dynamism and embeddedness, as well as access to organisational capital, human capital (Zhou et al, 2013), social capital and the more political and institutional roles of global institutions (Schemeil, 2013). However, it is less clear who plays which roles to span and mobilise multi-dimensional contextual boundaries (Gupta et al, 2006;Nosella et al, 2012).…”
Section: Journal On Chain and Network Science 15 (2015)mentioning
confidence: 99%
“…The systematic literature review by Seeck and Diehl (2016) indicated the importance of HCWSs for innovation, and our review comes to a similar conclusion for HCWPs and IWB. Zhou et al (2013) argued that a high-commitment philosophy is beneficial in achieving innovation outcomes because practices such as employment security establish employees' psychological commitment to the organisation and motivate employees to take risks.…”
mentioning
confidence: 99%